Late Roman Local production in south western Noricum: Municipium Claudium Aguntum – a case study - Auer, Martin (Rei Cretariae Romanae Fautorum Acta, 2012)
The Municipium Claudium Aguntum is situated in the southwestern part of the Roman Province of Noricum, nowadays eastern tyrol, austria. the town was founded as a municipium in Claudian times and the location of the settlement was still known in literature at the beginning of the 7th century.